TOURISM CLUSTERS AND INNOVATION SECURITY: DIALECTICS IN THE WESTERN BORDER REGIONS OF RUSSIA - Vasilisa Valeryevna GOROCHNAYA; Andrey Sergeevich MIKHAYLOV; Anna Alekseevna MIKHAYLOVA; Angelina Petrovna PLOTNIKOVA (GeoJournal of Tourism and Geosites, 2020)
The article provides an assessment of tourism sector impact on regional innovation growth. The research focuses on the border regions of Western Russia experiencing the highest pressure on innovation security under the current situation of losing the established cross-border collaboration ties. The scope of the study covers Bryansk, Kaliningrad, Leningrad, Murmansk, Pskov, and Smolensk regions, Krasnodar Krai, the Republic of Karelia, the city of Saint-Petersburg as nucleus of metropolitan agglomeration. The regions are analysed for their tourism development dynamics, capturing tendencies of growth and strategic development priorities. Both interconnection and independence between tourism and innovation dynamics are identified, resulting in a typology. The best practices pointed out within the selected case studies are assessed as to be transmitted to other regions.